Interview with Russ Tripp and Herb Hammond - Linn-Benton Community College (1992)
"This conversation between Jon Carnahan, President of Linn-Benton Community College, and Herb Hammond and Russ Tripp, leaders in the formation and early years of the college, was recorded in one sitting at Mr. Carnahan's home on February 6, 1992 in Albany Oregon."